Digital Economic Transformation and the Challenge of Social Inequality in Southeast Asia - Fikram, Fikram; Ispini, Sri; Hadi, Samsul (Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
This study explores the dynamics of digital economic transformation and its implications for social inequality in Southeast Asia using a qualitative, literature-based approach. The research synthesizes secondary data from recent academic studies, policy reports, and institutional publications to analyze how digitalization shapes regional economic structures and equity outcomes. Findings indicate that digital transformation has driven post-pandemic economic recovery and innovation; however, it has also deepened disparities in access, digital literacy, and participation among ASEAN member states. The uneven implementation of regional frameworks such as the ASEAN Digital Masterplan 2025 and the Digital Economy Framework Agreement highlights persistent gaps in governance and infrastructure readiness. Moreover, gender and spatial inequalities continue to limit inclusive digital engagement, especially in rural and low-income contexts. The study concludes that for digital transformation to contribute to equitable and sustainable development, Southeast Asian governments must prioritize human capital investment, regulatory harmonization, and social justice within their digital strategies.